Analisis Perundungan Siber Flaming atas Komunikasi Penggemar BTS di Twitter - Handrian Taufik; Maulana Rezi (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2022)
In the current digital era, Popular Culture is a culture that is widely consumed by the public. The presence of social media also makes the access to popular culture such as K-Pop become easier. An example can be seen in the habit of fan accounts on Twitter which builds a communication process both with idol artists and with fellow fans. The interactions carried out included discussions regarding idol artists, works, idols' daily activities, and others. However, this interaction also does not rule out negative interactions such as cyberbullying. Using a Virtual Ethnography approach, this study was conducted to find the theme of the flaming message transmitted by fans of the BTS or ARMY group as a specific understanding of the implications of cyberbullying events on Twitter. This study uses software, namely ATLAS.ti to assist the process of collecting research data to the process of data analysis. The results of this study found four themes of cyberbullying messages transmitted by ARMY on Twitter, namely flaming cyberbullying messages with the themes of attacking, cursing, condescending, and laughing. This study also found that a flaming message is a form of defensive action taken by ARMY in defending their idol artist which is rooted in the fanaticism of fans. This research is expected to be able to increase digital literacy for social media users, especially Twitter, increase awareness to wisely use social media, and become a reference for further research.